Beam Splitters Fabricated by Nonlinear Focusing of Femtosecond Laser Writing in Pure YAG Crystal - Wu, Pengfei; Yang, Senchi; Ren, Yingying; Liu, Hongliang (Frontiers in Physics, 2021)
We report on the fabrication of waveguides and beam splitter in pure YAG crystal by femtosecond laser directly writing (FLDW). During the femtosecond laser writing process, positive refractive index is induced through the nonlinear-focusing above the focus position, resulting in unusual guiding cross-sectional configuration. The supported guiding modes at 632.8 nm are measured and analyzed by the end-face coupling system. The propagation loss can be as low as 1.9 dB/cm for the single-line waveguide. Different from the geometry of traditional fs-laser modified area, this novel structure might offer a new approach in the quest to the integrated photonics.